PERAN PENYULUH PERTANIAN DALAM BUDIDAYA PADI SALIBU DI KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Tanjung, Heri Bachrizal; Wahyuni, Sri; Ifdal, Ifdal (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
Agricultural extension acts as agents of change directly related to farmers. Likewise, the role of agricultural extension in Tanah Datar District is in the salibu extension program, so this study aims to describe the role of agricultural extension in salibu cultivation in Tanah Datar District. The research was conducted from August to October 2018 in Tanah Datar District, West Sumatera. This type of research was descriptive research that was designed qualitatively, where the method used was focus group discussion (FGD). The data source was selected purposively (intentionally) consisting of 17 agricultural extension workers in Tanah Datar District, which consisted of district extension agents, coordinator extension, and agricultural extension agents. The results showed that the role of agricultural extension in the salibu cultivation in Tanah Datar was as a motivator for farmers in conducting salibu cultivation. Extensions became counselors and agents of rice transfer technology so that farmers became aware, willing, capable, and skilled in conducting millet rice cultivation. Extensions convey the advantages of salibu, carry out demonstration plots, conduct guidance and provide training activities through field schools, as well as mentoring maintenance untill harvest.